A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina - Rodríguez, Mónica S.; Miquelarena, Amalia M. (Zootaxa, 2005)
Rineloricaria misionera is a new species from the Paraná and Uruguay River basins, Misiones, Argentina. The new species is distinguished from all others in the genus by the following combination of characters: anterior abdomen covered by plates, except for the area corresponding to the pectoral girdle, which usually lacks plates, when present in this region, plates are relatively small and few; posterior abdomen with a well-developed preanal plate, bordered anteriorly by a series of 3–5 usually polygonal plates; premaxillary and dentary teeth with asymmetric cusps; uppermost caudal ray not prolonged in a filament; and snout tip with an oval naked area not reaching the last pore of the infraorbital sensory canal.